Morphological and Optical Characterization of Sol-Gel Synthesized Ni-Doped ZnO Nanoparticles. Issue 205 (12th February 2020) - Prerna,; Arya, Sandeep; Sharma, Asha; Singh, Bikram; Tomar, Amit; Singh, Suram; Sharma, Rakesh
Abstract: In this work, Ni-doped ZnO nanoparticles (NPs) were successfully synthesized by sol-gel method. The as-synthesized nanoparticles were characterized to investigate their morphology, structure, purity and optical properties. XRD analysis confirmed the formation of nanoparticles with average particle size of approx. 30 nm. SEM observations show the agglomeration of nanoparticles. The purity of the as-prepared NPs was confirmed by EDX analysis. The defect states were revealed from the photoluminescence (PL) spectra. The overall results obtained indicate that Ni-doped ZnO nanoparticles are promising candidate to fabricate nanoscale optoelectronic devices due to their wide band gap and excellent UV emission properties.